Antithrombin Cambridge II (Ala384Ser): Clinical, Functional and Haplotype Analysis of 18 Families - Perry, D. J.; Daly, M. E.; Tait, R. C.; Walker, I. D.; Brown, K.; Beauchamp, N. J.; Preston, F. E.; Gyde, H.; Harper, P. L.; Carrell, R. W. (Thrombosis and Haemostasis, 1998)
Thirty-one individuals from 18 unrelated families with antithrombin deficiency have been identified as having a single point mutation within codon 384 (13268 GCA→TCA) resulting in an alanine to serine substitution. Six families (11 individuals) were identified by the screening of individuals with thromboembolic disease or with a family history of thromboembolic disease, whilst the remaining 12 families (20 individuals) were identified by screening of asymptomatic blood donors. Four individuals had a history of venous thrombotic disease, a further 2 gave a history of superficial thrombophlebitis but the remaining 25 individuals were asymptomatic. Affected individuals demonstrated normal immunological levels of antithrombin but a decrease in anti-IIa activity in the presence of heparin. Haplotype analysis was used to examine the possibility of a founder effect to explain the high frequency of this non-CpG mutation. 29/31 individuals showed a single common “core” haplotype, the only variation existing in the number of copies of an (ATT)n repeat polymorphism – 13, 14, 15 or 17. The results suggest that at most there are four independent origins for this mutation.